An unexpected retroperitoneal paraganglioma with hypertensive crisis during surgical resection: a case report and literature review - Shen, Meng-Ting; Xuan, Ye; Chen, Kai-Yu; Lu, Xin-Lei; Lei, Wei-Ping; Huang, Ya-Qin; Sun, Jian-Liang (Frontiers in Oncology, 2025)
Retroperitoneal paraganglioma is an extremely rare tumor. Its atypical clinical presentations often lead to missed and misdiagnosis. Here, we report a 60-year-old male with unexplained weight loss and a medical history of hypertension and diabetes. Preoperative evaluations showed a left lower abdominal mass, considered as a malignant gastrointestinal stromal tumor or a leiomyosarcoma. During the laparoscopic resection of tumor, his blood pressure fluctuated significantly, especially with the tumor manipulation that caused hypertensive crisis. Phentolamine infusion was given to control the blood pressure, and the tumor was removed under the open abdominal surgery. Further laboratory tests on catecholamine levels and postoperative histopathology confirmed the diagnosis of retroperitoneal paraganglioma. Follow-up showed good recovery with no complications. Paraganglioma should be considered when an unknown mass with severe blood pressure fluctuations is encountered during surgery. Careful preoperative preparations and close intraoperative monitoring should be applied in patients with suspected paraganglioma.